Calvo contracts: Optimal indexation in general equilibrium - Vo Phuong Mai Le; Patrick Minford (Cardiff University, Cardiff Business School, 2007)
Calvo contracts, which are the basis of the current generation of New Keynesian models, widely include indexation to general ináation. We argue that the indexing formula should be expected ináation rather than lagged ináation. This is likely to optimise the welfare of the representative agent in a general equilibrium model of the New Keynesian type. The economy behaves under rational indexation is similar to a New Classical model, with shocks producing an immediate áuctuation in both prices and output followed by a fairly rapid return to steady state. The monetary policy that targets price level brings a greater economic stability.
Keywords: F41; F42; E42; 330; Calvo contracts; general equilibrium; rational indexation; Geldpolitik; Inflationsrate; Indexierung; Wohlfahrtsanalyse; Keynesianismus; Nichtlineares Verfahren